2016
DOI: 10.21125/edulearn.2016.1104
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mooc for Teaching Employability Skills to Foreign Students in Germany

Abstract: The outcomes of educating foreign students at German universities falls behind stakeholder expectations. While foreign students are typically interested in staying in Germany to work, two-thirds do not succeed in securing full-time employment. This paper introduces the Employability Skills MOOC (Massive Open Online Course) that aims at alleviating this problem by using a scalable online medium to enhance especially foreign learners' competencies needed for career success in Germany. The paper reviews the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this research, Grounded Theory is applied to explore factors that may influence the job-seeking success of foreign graduates and thus provide insights into a previously insufficiently understood phenomenon. The Grounded Theory of Corbin and Strauss ([7] p. [18][19] is anchored in the philosophy of pragmatism, in which ideas refer to possibilities to act and 'knowledge arises through … acting and interacting of selfreflective beings'. As the authors are international higher education practitioners, they have an inherent professional interest in enhancing foreign graduate employability; as well as previous experience in related educational practices.…”
Section: Substantive Grounded Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, Grounded Theory is applied to explore factors that may influence the job-seeking success of foreign graduates and thus provide insights into a previously insufficiently understood phenomenon. The Grounded Theory of Corbin and Strauss ([7] p. [18][19] is anchored in the philosophy of pragmatism, in which ideas refer to possibilities to act and 'knowledge arises through … acting and interacting of selfreflective beings'. As the authors are international higher education practitioners, they have an inherent professional interest in enhancing foreign graduate employability; as well as previous experience in related educational practices.…”
Section: Substantive Grounded Theorymentioning
confidence: 99%
“…None of the participants demonstrated a systematically managed and reflective job application process that would make use of a database of found opportunities and sent applications, scheduled follow-up calls or a journal to record experiences. Kapanen et al [18] observed that universities may not comprehensively provide such skills and it often rests on the individual to acquire them [18].…”
Section: Strategies For Job Acquisitionmentioning
confidence: 99%